Microbiome Differences in Colorectal Cancer Patients and Healthy Individuals: Implications for Vaccine Antigen Discovery - Ibeanu GC; Rowaiye AB; Okoli JC; Eze DU (ImmunoTargets and Therapy)
Gordon C Ibeanu,1 Adekunle B Rowaiye,1,2 Joy C Okoli,1 Daniel U Eze1 1Department of Pharmaceutical Sciences, North Carolina Central University, Durham, NC, 27707, USA; 2Department of Agricultural Biotechnology, National Biotechnology Development Agency, Abuja, NigeriaCorrespondence: Adekunle B Rowaiye, Department of Pharmaceutical Sciences, North Carolina Central University, Durham, NC, 27707, USA, Tel +1-9193812004, Email adekunlerowaiye@gmail.comBackground: Colorectal cancer (CRC) is the third most prevalent cancer worldwide, with numerous risk factors contributing to its development. Recent research has illuminated the significant role of the gut microbiota in CRC pathogenesis, identifying various microbial antigens as potential targets for vaccine development.Aim: This review aimed at exploring the potential sources of microbial antigens that could be harnessed to create effective CRC vaccines and understand the role of microbiome-CRC interactions in carcinogenesis.Methods: A comprehensive search of original research and review articles on the pathological links between key microbial candidates, particularly those more prevalent in CRC tissues, was conducted. This involved extensive use of the PubMed and Medline databases, as well as the Google Scholar search engine, utilizing pertinent keywords. A total of one hundred and forty-three relevant articles in English, mostly published between 2018 and 2024, were selected.Results: Numerous microbes, particularly bacteria and viruses, are significantly overrepresented in CRC tissues and have been shown to promote tumorigenesis by inducing inflammation and modulating the immune system. This makes them promising candidates for antigens in the development of CRC vaccines.Conclusion: The selection of microbial antigens focuses on their capacity to trigger a strong immune response and their link to tumor presence and progression. Identifying and validating these antigens through preclinical testing is essential in developing a CRC vaccine.Plain Language Summary: Colorectal cancer (CRC) is a common and serious disease that affects many people worldwide. Research has shown that the bacteria and other microorganisms in our gut play a significant role in the development of CRC. This review aimed to identify specific microbial targets that could be used to develop effective vaccines against CRC.The researchers searched through numerous scientific articles and found that certain bacteria and viruses are more commonly found in CRC tissues and promote tumor growth by causing inflammation and affecting the immune system. These microbes have the potential to be used as antigens in CRC vaccines.The identification of these antigens is a crucial step towards developing a vaccine that can prevent or treat CRC. Further research is needed to validate these findings and move closer to creating an effective vaccine against this disease.In simpler terms, this research is exploring how the gut microbiome contributes to colorectal cancer and searching for specific targets to develop a vaccine that can help prevent or treat the disease.Keywords: colorectal cancer, microbe, antigen, vaccine, tumor